Hubungan Asupan Serat Dan Vitamin C Dengan Kadar LDL Dan HDL Pada Pasien Jantung Koroner Rawat Inap Di RSUD Dr. Moewardi - Aprionika, Fidara, Ririn Yuliati, SSiT., M.Si (2016)
Background : Fiber has a rule in decreasing cholesterol level. Vitamin C as an antioxidation has a rule in body protection caused by free radical whom causes a degenerative disease such as heart attack. Coronary heart disease happens from a blood artery obstruction. Purpose : To asses the correlation between fiber and vitamin C intake LDL and HDL levels in coronary heart disease patients at DR. Moewardi hospital. Method of the research : This research used observation method with cross-sectional design and used 43 subjects. The data collecting included food consumption were obtained through food recall, while LDL and HDL levels were obtained through medical record. The data analysist used pearson product moment tests. Result : Most medical patients were males (51,2%). Most of the medical patients had bad fiber intake (95,3%), bad vitamin C intake (97,7%), unusual LDL level (83,7%) and unusual HDL level (72,1%). There were no correlations between fiber intake and levels of LDL and HDL in patients with coronary heart disease respectively (p) value were 0,937 and 0,252. There were no correlations between vitamin C intake and levels of LDL and HDL in patients with coronary heart disease respectively (p) value were 0,752 and 0,653. Conclusion : There were no correlations between fiber and vitamin C intakes and levels of LDL and HDL in patients with coronary heart disease. Latar Belakang : Serat makanan berperan dalam menurunkan kolesterol. Vitamin C sebagai antioksidan berperan dalam perlindungan tubuh terhadap kerusakan akibat radikal bebas yang mengakibatkan penyakit degeneratif seperti jantung koroner. Penyakit Jantung Koroner (PJK) merupakan gangguan fungsi jantung akibat dari penyumbatan pembuluh darah. Tujuan : Untuk mengetahui hubungan asupan serat dan vitamin C dengan kadar LDL dan HDL pasien penyakit jantung koroner di RSUD Dr. Moewardi. Metode Penelitian : Penelitian ini menggunakan studi observasi dengan pendekatan Cross Sectional dengan jumlah 43 sampel. Data yang dikumpulkan meliputi asupan makan diperoleh dengan recall konsumsi makanan dan kadar LDL dan HDL dari rekam medis. Analisis data menggunakan Pearson Product Moment. Hasil : Sebagian besar pasien adalah laki-laki (51.2%). Seluruh pasien memiliki asupan serat tidak baik (95.3%), asupan vitamin C tidak baik (97.7%), kadar LDL tidak normal (83.7%) dan kadar HDL tidak normal (72,1%). Tidak terdapat hubungan antara asupan serat dengan kadar LDL dan HDL pada pasien penyakit jantung koroner (p=0.937) dan (p=0.252). Tidak terdapat hubungan antara asupan vitamin C dengan kadar LDL dan HDL pada pasien penyakit jantung koroner (p=0.752) dan (p=0.653). Kesimpulan : Tidak terdapat hubungan antara asupan serat dan vitamin C dengan kadar LDL dan HDL pada pasien penyakit jantung koroner.